The anchoring of inflation expectations in the short and in the long run - Dieter Nautz; Aleksei Netšunajev; Till Strohsal (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
His paper introduces structural VAR analysis as a tool for investigating the anchoring of inflation expectations. We show that U.S. consumers' inflation expectations are anchored in the long run because macro-news shocks are long-run neutral for long-term inflation expectations. The identification of structural shocks helps to explain why inflation expectations deviate from the central bank's target in the short run. Our results indicate that the recent decline of long-term inflation expectations does not result from deanchoring macro-news but can be attributed to downward adjustments of consumers' expectations about the central bank's inflation target.
Keywords: E31; E52; E58; 330; Inflation Expectations; Michigan Survey; Structural VAR; Markov-Switching Heteroskedasticity